Between FOMO and Qana’ah: Ibn Qayyim’s psychospiritual framework for muslim mental health in the digital era - Irawan, Deni; Mujib, Abd.; Ubaidillah, Ubaidillah (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2025)
Abstract: The widespread phenomenon of Fear of Missing Out (FOMO) among Muslim social media users has been associated with heightened anxiety and other mental health challenges, revealing a critical gap in psychological interventions that often neglect spiritual dimensions. This study aims to explore the relevance of the Islamic concept of qana’ah as articulated by Ibnu Qayyim Al-Jawziyyah, positioning it as a spiritual countermeasure to FOMO within the framework of tazkiyatun nafs (purification of the soul). Employing a narrative review approach, this research synthesizes insights from classical Islamic texts and contemporary empirical studies to construct an integrative perspective. The findings indicate that FOMO contributes to psychological distress and reduced quality of life, whereas qana’ah, cultivated through practices such as muhasabah (self-reflection), gratitude, and tawakkal (trust in God), enhances psychological well-being and resilience in digital contexts. This study proposes a novel framework that bridges modern psychology and Islamic wisdom, while recommending future empirical research to validate the practical effectiveness of qana’ah-based interventions across diverse Muslim populations. Keywords: FOMO; Qana’ah; mental health; Islamic psychology; Ibnu Qayyim Copyright ©2025. The Authors. Published by Psikoislamika: Jurnal Psikologi dan Psikologi Islam. This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0